Health Literacy for Chronic Illness Prevention among Adults in Bangkok Metropolitan: A Case Study of Conditions for Building Health Literacy - Lhaosupab, Niramon; Prueksaanantakal, Naphatthorn; Yaprom, Chulaporn; Chiangkhong, Araya (Nursing Research and Innovation Journal, 2021)
As a case study, this qualitative research aimed to understand the conditions of promoting health literacy on preventing chronic illnesses in adults. Data were collected using in-depth interviews among 15 adults aged 18-59 years who lived in Bangkok and obtained a high health literacy score assessed by the Thai version of the Chronic Illness Prevention Health Literacy Scale. Data were analyzed using content analysis. The results showed that conditions of promoting health literacy to prevent chronic illnesses in adults consisted of two main points as individual and external conditions. The individual conditions included: 1) learning health information from the effects of chronic illness, 2) increasing self-confidence in health communication. The external conditions had: 1) social support for self-care, 2) contents and methods of presenting health media for building cognitive skills. The findings could be used to promote health literacy in preventing chronic illness in adults. Keywords: Adults, Health literacy, Preventing chronic illness